Experimental and numerical studies on the two "lock-in" regions characteristic of vertical vortex-induced vibration of Π-shaped composite bridge deck. Issue 228 (September 2022) - Li, Jiawu; Wu, Peng; Hao, Jianming; Pan, Hui
Abstract: The Π-shaped bridge deck may easily occur vertical vortex-induced vibration, due to the bluff body aerodynamic configuration, which may cause the uncomforting of vehicles and pedestrians on the bridges. The present study mainly focused on the two "lock-in" regions characteristics of vertical vortex-induced vibration (VIV) of Π-shaped bridge deck, which can reveal the aerodynamic mechanism of vibration mitigation countermeasures. The vertical VIV response of original Π-shaped deck and those with different countermeasures are experimentally investigated detailly. Computational fluid dynamics (CFD) method is employed to numerically simulate the surrounding flow field of original girder section and those with different aerodynamic countermeasures. The numerical method is firstly verified through the comparison with the results of corresponding experimental results obtained in wind tunnel test. Afterwards, the flow pattern and vortex structure around the girder section simulated by CFD are utilized to interpret the effects of the mitigation countermeasures. The numerical results show that: (a)The vibration mitigation effect in the first vortex "lock-in" region is not sensitive to the position of the aerodynamic countermeasures, while the vibration mitigation effect in the second "lock-in" region is more sensitive to the position of the aerodynamic countermeasures; (b) The phase of aerodynamic lift and displacement response is close to synchronization in the ascending section of the VIV amplitude, greater than 90 ° in the descending section, and close to 180 ° outside the vortex-induced resonance range. The first vertical VIV region is related to the "Karman vortex street" at the trailing edge of the section, while the second vertical VIV region is related to the vortex shedding at the lower edge of the front end of the section and the secondary vortices on the upper surface. Highlights: The aerodynamic mechanism of mitigation countermeasures on Π-shaped bridge deck was systemically investigated. The vibration mitigation effect in the second "lock-in" region is more sensitive to the position of the aerodynamic countermeasures. The phase of aerodynamic lift and displacement response is discussed in different vortex-induced resonance region.